UPAYA PENINGKATAN KEMAMPUAN GURU UNTUK MENGGUNAKAN MEDIA PEMBELAJARAN DALAM PROSES PEMBELAJARAN MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH SD NEGERI 63 PEKANBARU: Teacher Ability Improvement Efforts to Use Learning Media in Learning Process Through Academic Supervision Of School Heads of SD Negeri 63 Pekanbaru - Asnawati Asnawati (UIR Press, 2019)
This study aims to help improve the competency of 63 Pekanbaru Elementary School teachers in the field of operating media in the learning process so that students are able to achieve minimum completeness criteria. As the subject in this study, elementary school teachers were horrified by 63 new sensitivities, totaling 13 people. The formulation of the problem in research I is whether the ability to use instructional media by teachers of SD 63 Pekanbaru can be improved through the academic supervision of the principal ?. The technique of data collection is done by filling in the observation sheet during the research action process by the supervisor so that qualitative data will be obtained as a result of research with performance indicators said to be successful if the average score is ≥75. The results of the study in cycle 1 obtained a percentage with a percentage score of 73% with a fairly good classification in the classification range (71–80). In the second cycle the percentage of success was obtained with a percentage score of 85% with a good classification in the classification range (81-90). Reflections on cycle 2 activities were successful because 85 were above the performance indicator> 75. The increase in understanding of the use of learning media from cycle I to cycle II. Weaknesses in the first cycle after being corrected in cycle II and reached a perfect level so that it can improve satisfactory results with good classification. Thus through academic supervision by the principal can improve the ability of teachers in understanding and using learning media in the SDN 063 Pekanbaru school